The Evaluation of Memantine Effect on Tinnitus Severity - Babak Pourayyoubi; Alireza Rezaei‐Ashtiani; Javad Javaheri; Mohsen Ebrahimi Monfared; Farzad Zamani (Brain and Behavior, 2025)
ABSTRACT Purpose Tinnitus is a common condition where a person perceives sound despite there being no external auditory stimuli. It is proven that overexpression of NMDA (N‐methyl‐d‐aspartate) glutamate receptors increases the sensitivity of neurons to glutamate transmission, creating a destructive cycle of excitotoxicity. NMDA receptor antagonists, such as memantine, seem to be effective in treating tinnitus. This study aimed to examine the effectiveness of memantine as a treatment for tinnitus in a double‐blind randomized placebo control clinical trial. Methods The participants were patients with tinnitus. A total of 70 patients were randomly assigned into two groups, intervention and a placebo, with an equal number of patients in each group. Both groups received conventional treatment with cinnarizine at a dose of 25 mg twice a day. In the intervention group, memantine was added to cinnarizine with starting dose of 5 mg. Tinnitus Severity Index (TSI) and Numeric Rating Scale (NRS) were recorded before and after study in both groups. Findings There was no significant difference in the initial mean of NRS and TSI scores between two groups. After treatment, the mean NRS and TSI scores were significantly lower in the intervention group. Although the changes in mean NRS scores were significant in both groups at the end of study but only the mean TSI scores were significantly decreased in the intervention group. Conclusion On the basis of these findings, it is suggested that memantine may have remarkable effect in reducing tinnitus and its discomfort.